DEVELOPMENT OF AGRIBUSINESS PLACES ON PALU RIVERSIDES - Wildani Pingkan Suripurna Hamzens; Meidy Widayanto Moestopo (AGROLAND The Agricultural Sciences Journal (e-Journal), 2020)
Agribusiness may potentially develop on Palu Riversides. This research aims to formulate a sustainable agricultural spatial innovation for the Development of Agribusiness Places on Palu Riversides. The methods used for this study were field observation, satellite image map observation, and literature review. The results showed that the implementation of sustainable agriculture through the development of agribusiness places in urban areas could take advantage of the open spaces designated as green open space zone on the Palu Riversides, namely the River Green Area which is outside the riparian zone, the river overflow runoff area. To achieve this objective, it requires ability to innovate in spatial planning so that an urban agricultural area that is neatly arranged into an agribusiness places can also be developed into one of the city landmark.